2011
DOI: 10.1111/j.1755-3768.2011.02307.x
|View full text |Cite
|
Sign up to set email alerts
|

Optos‐guided pattern scan laser (Pascal)‐targeted retinal photocoagulation in proliferative diabetic retinopathy

Abstract: . Purpose:  To investigate the clinical effects and safety of targeted pattern scan laser (Pascal) retinal photocoagulation (TRP) in proliferative diabetic retinopathy (PDR). Methods:  Prospective and non‐randomized study of 28 eyes with treatment‐naive proliferative diabetic retinopathy (PDR). Single‐session 20‐ms‐Pascal TRP strategy applied 1500 burns to zones of retinal capillary non‐perfusion and intermediate retinal ischaemia guided by wide‐field fluorescein angiography (Optos). Main outcome measures at 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
58
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(61 citation statements)
references
References 31 publications
2
58
0
1
Order By: Relevance
“…PDR regression with reduced NV leakage was seen in 76% of eyes at 12 weeks. 48 Repeat TRP was needed in 10 eyes (37%) by 12 weeks. At 6 months, complete PDR regression was seen in 10 eyes (37%) and partial regression in an additional 9 eyes (33%).…”
Section: Uwf Imaging and Targeted Retinal Photocoagulationmentioning
confidence: 99%
“…PDR regression with reduced NV leakage was seen in 76% of eyes at 12 weeks. 48 Repeat TRP was needed in 10 eyes (37%) by 12 weeks. At 6 months, complete PDR regression was seen in 10 eyes (37%) and partial regression in an additional 9 eyes (33%).…”
Section: Uwf Imaging and Targeted Retinal Photocoagulationmentioning
confidence: 99%
“…Reddy et al [23] were the first to explore this field, and they reported NV regression in 2 eyes treated by means of TRP with no PRP-related side effect. Subsequently, Muqit et al [24,25] prospectively confirmed on a larger sample that TRP and PRP have the same efficacy on NV regression, but the former causes higher reduction in CMT. Figure 4 shows the DR downgrade after TRP.…”
Section: Ultra-wide Field In Drmentioning
confidence: 91%
“…Other studies have demonstrated the association between peripheral retinal nonperfusion and the occurrence of neovascularization, macular ischemia, and diabetic mac-http://dx.doi.org/10.21561/jor.2016.1.1.1 ular edema (DME) [20,[31][32][33]. Another study suggested that UWF FA will be used to guide the management of DR [34]. UWF-guided targeted retinal photocoagulation to areas of nonperfusion with successful regression of retinal neovascularization.…”
Section: Clinical Applications Of Ultra-widefield Imaging Diabetic Rementioning
confidence: 99%